Problem-Based Learning Using Media Quizizz to Enhance Critical Thinking SD N 1 Kembaran Kulon Academic Year 2024/2025 - Parwati Parwati; Wanda Nugroho Yanuarto (Proceedings Series on Social Sciences & Humanities, 2025)
The purpose of this study is to investigate the impact of problem-based learning using quiz media on the critical thinking skills of SD Negeri 1 Kembaran Kulon students in the 2024/2025 academic year. This is an experimental study that uses a pretest-posttest control group design. The cluster random sampling technique was used. The cluster random sampling technique was used. This study included all fourth-grade pupils at SD N 1 Kembaran Kulon, using samples from class IV a (experimental class) and class IV b (control class). The instrument utilized was a science process skills test consisting of multiple-choice reasoned questions that were initially validated for validity, reliability, discrimination power, and question difficulty level. The pretest homogeneity test revealed that the experimental and control classes had similar baseline abilities, implying that the treatment's effect was determined by the posttest. The analysis equipment test revealed that the posttest data were normally distributed and homogeneous, so the parametric t-test pooled variance statistic with two-tailed t-test criteria was used, with the t count of 5.38 and the t table of 1.99 at a 5% significance level. If - ttable < tcount > + ttable, Ho is rejected while Ha is approved. As a result, it is possible to conclude that problem-based learning through quiz media has an impact on the critical thinking abilities of SD Negeri 1 Kembaran Kulon during the 2024/2025 academic year.